The effects of mentor support on Ed.D students’ research creativity: mediating roles of research self-efficacy and learning engagement - Miao, Haifei; Zhao, Lixing; Wang, Zhigang (Frontiers in Psychology, 2025)
IntroductionDoctor of education (Ed.D) is a professional degree designed to cultivate highly specialized professionals in education, teaching, and educational leadership. Ed.D holds a crucial position within the higher education system, with its core mission being the cultivation of high-quality talent who possess strong research creativity. However, limited research has specifically addressed how to enhance the research creativity of Ed.D students in higher education.MethodsThis study utilized a structural equation modeling approach to investigate the influence of mentor support on Ed.D students research creativity, with a focus on the chain mediating effects of research self-efficacy and learning engagement. A sample of 366 Chinese Ed.D students was surveyed using validated scales for mentor support, research self-efficacy, learning engagement, and research creativity.ResultsThe findings indicate that mentor support is significantly positively correlated with the research creativity of Ed.D students; research self-efficacy and learning engagement serve as mediators in the relationship between mentor support and research creativity. Moreover, the average scores for Ed.D students’ research self-efficacy and learning engagement are comparatively low, with male students reporting higher levels of research self-efficacy and research creativity on average.DiscussionThese results provide empirical support and practical recommendations for enhancing the research ability of Ed.D students.